Production, optimization and probiotic characterization of potential lactic acid bacteria producing siderophores - Panda, Smita H. (AIMS Microbiol, 2017)
The aim of the study was to characterize the probiotic qualities and siderophore production of Enterococcus and Bacillus isolates for possible application for iron nutrition in human and animals strains were selectively isolated from different dairy sources and infant faecal matter. Isolates SB10, JC13 and IFM22 were found to produce maximum siderophore ranging from 65–90% at an optimum pH 7, incubation period of 96 h, agitation speed of 150 rpm and inoculum volume of 15%. SB10 and JC13 were found to show high homology with Enterococcus spp. and IFM22 with Bacillus spp., using partial 16S rRNA sequencing and biochemical characterization. All the three isolates produced hydroxymate type of siderophores under iron stressed conditions and screened for probiotic characters as per WHO guidelines. Strains have shown excellent tolerance to acid, bile salt, sodium chloride and phenol. They were non-haemolytic in nature and exhibited high hydrophobicity and autoaggregation. Our isolates proved to be potent probiotic strains due to their survival under highly acidic conditions and higher tolerance to bile salt. In addition, its colonization efficiency was proved by exhibiting high autoaggregation and hydrophobicity.